2013
DOI: 10.1371/journal.pone.0076679
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Protects Vascular Endothelium against Atherosclerotic Inflammatory Reaction via Akt/eNOS and Nuclear Factor-κB Pathways

Abstract: ObjectiveAtherosclerosis is considered a chronic inflammatory disease, initiated by activation and dysfunction of the endothelium. Recently, progranulin has been regarded as an important modulator of inflammatory processes; however, the role for prgranulin in regulating inflammation in vascular endothelial cells has not been described.Method and ResultsSignaling pathways mediated by progranulin were analyzed in human umbilical vein endothelial cells (HUVECs) treated with progranulin. Progranulin significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…# P < 0.05 versus controls. Notably, it is known that progranulin reduces the expression of TNFa and MCP-1 in vascular endothelium (Hwang et al, 2013). Therefore, low TNFa or unchanged MCP-1 CSF levels we observed in GRN patients may be linked to haploinsufficiency.…”
Section: Discussionmentioning
confidence: 68%
“…# P < 0.05 versus controls. Notably, it is known that progranulin reduces the expression of TNFa and MCP-1 in vascular endothelium (Hwang et al, 2013). Therefore, low TNFa or unchanged MCP-1 CSF levels we observed in GRN patients may be linked to haploinsufficiency.…”
Section: Discussionmentioning
confidence: 68%
“…The BCECF/AM-labeled THP-1 cells were incubated with stimulated HUVECs for 30 min, and washed using PBS. The levels of attached THP-1 cells were analyzed using a fluorescence microscope and Spectrofluorometer (PerkinElmer, Bridgeville, PA, USA) at 485 nm/520 nm (Hwang et al, 2013).…”
Section: Adhesion Ability Of Monocytic Thp-1 Cells To Huvecsmentioning
confidence: 99%
“…The growth factor PGRN has been shown to inhibit TNF-a directly (Liu, 2011;Tang et al, 2011;Hwang et al, 2013); in this study, we explored the blocking effect of PGRN on the TNF-a-mediated inhibition of osteoblast differentiation. We established a C2C12 osteoblast differentiation cell model via BMP-2 induction, where we confirmed that PGRN effectively blocks the TNF-a-mediated inhibition of alkaline phosphatase activity and bone mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study described the protective effect of PGRN on Alzheimer's disease, as well as its positive role in wound healing (He et al, 2003;Pereson et al, 2009). Further studies have reported that PGRN inhibits TNF-a and plays a key role in the pathogenesis of atherosclerosis and rheumatoid arthritis (Liu, 2011;Tang et al, 2011;Hwang et al, 2013). However, the exact effects of PGRN on bone tissue remain to be validated.…”
Section: Introductionmentioning
confidence: 99%